The printing industry in Iloilo City an investigation and analysis - Palisan, Rora M.; Sevilla, Maria Nelia Lourdes G.; Supe, Sheryll E.; Tibajares, Katheryn C.; Trabajador, Lyndel T.
This study entitled "The Printing industry in Iloilo City : An investigation and Analysis' is generally one of an investigative type that thereafter provides meaningful relation to an exegesis of the present status of the printing industry in Iloilo City. This study covers about twenty out of thirty team players or printing companies in the industry contemplated in light of the different aspects of the printing business belonging to it--organization and administration, production and operation, research and technological factors, marketing and finance. Focus is given on how well the industry performs in terms of the maximization of wealth it can bring about--thus, profitability-- and on its technological advancement and stability to answer the problem of this study as to status of the Printing Industry in Iloilo City, how far has it gone in terms of technology, stability, and profitability, and the standard that regulates the operation of the team players and its effect in the industry. This study uses both primary and secondary data. Primary data gathering is made by exhausting all other data-gathering techniques possible. Among others are, interviews with the managers or owners in the printing business, giving out a questionnaire to the respondent printing firms, and taking some office/manufactory visits and making whetted observation thence. Secondary data gathering is primary done by library research. This study employs, insofar are applicable, both quantitative and qualitative analytical tools. The result of the study shows that the printing industry in Iloilo City is advancing or improving in terms of technology yet slowly. There are no standards that regulate the operation of the industry and because of this price-war among team players is prevalent. With the foregoing results, the researchers recommend that there must be a very strong printers association to set operation standards and protect the print operators, the government should make necessary intervention in the printing industry, printer operators should invest more in new machineries and continuous regular training shall be made available to both the printer owners or operators and their production staff.